Economic Evaluation Of Cetuximab for Metastatic Colorectal Cancer (mCRC): A Protocol For Evidence Synthesis - Putri, Septiara; Setiawan, Ery; Saldi, Siti Rizny F.; Chandra, Levina; Megraini, Amila; P, Vetty Yulianty (Jurnal Ekonomi Kesehatan Indonesia, 2018)
Colorectal cancer is fairly common compared to other cancers. The incidence and mortality rates are predicted to increase globally. In some cases, cancer can be potentially spread to another organ or metastatic. One of recent available targeted therapies for metastatic colorectal cancer (mCRC) patient is Cetuximab (Erbitux ®), combined with chemotherapy. Despite clinical effectiveness, there is the importance of the evidence related cost-effectiveness of therapy. This study aims to summary, synthesize, and systematically review the economic evaluation studies of Cetuximab for metastatic colorectal cancer (mCRC). Model based economic evaluation of Cetuximab for metastatic colorectal cancer will be searched and included in the review based on specific eligibility criteria. Several electronic databases that will be used: Medline, Embase, Cochrane, National Institute of Health Research (NIHR) Center for Reviews and Dissemination. Full economic evaluation evidence will be summarized and critically appraised using Drummond as well as (Consolidated Health Economic Evaluation Reporting Standards (CHEERS) checklist. In terms of analysis, we will qualitatively appraise and present the studies that meet our inclusion and exclusion criteria. We are expected to summarize the quality and capture the valuable insights related to health economic evaluation studies of Cetuximab for mCRC patient.